Waris Pengganti Perspektif Kompilasi Hukum Islam - Hasbiyallah, Iklil; Dimyati, Yayat (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2024)
This study intends to analyze the background of determining the substitute inheritance as well as to map the philosophical meaning and maslahah contained in the law of replacement inheritance as regulated in the Islamic Law Compilation. This is a research study and types of literature data that revolve around the basics of a law to collect data, to analyze the author using deductive and descriptive methods. The results of this study indicate that the background for determining replacement inheritance law in the Islamic Law Compilation is based on justice and mutual benefit and in accordance with the needs of the Indonesian people. The stipulation of the law also does not violate Islamic law (Maslahah Mursalah), which is good deeds according to society but is not regulated in the text nor is there any prohibition from the texts. Meanwhile, the philosophical meaning of the determination of the substitute inheritance law in the Islamic Law Compilation is the achievement of family welfare, especially the successor heirs, who have been left by their parents. Thus, no party will be harmed and persecuted. And Maslahah contained in the law of substitute inheritance is the benefit that can be obtained from a substitute heir, so as to avoid the dangers that will befall in the form of poverty and poverty due to his parents having died first.